Influence of drying temperature on the chemical constituents of jaboticaba (Plinia Jaboticaba (Vell.) Berg) skin (Acta Scientiarum. Technology, 2014)
Jaboticaba is a fruit native to Brazil. Its skin represents up to 43% of the fruit and contains high levels of fiber, minerals and phenolic compounds. The use of the skin waste adds value to the fruit. However, one of the drawbacks of skin storage is the high water content, which requires drying processes to preserve the skin without leading to the loss of nutrients and antioxidants. The influence of different drying temperatures on the levels of nutrients and antioxidants was investigated. Jaboticaba (Plinia jaboticaba (Vell.) Berg, genotype Sabará) skins were lyophilized or dried at three temperatures (30, 45, and 60ÂºC, using food dryers). The skins were then ground, stored (protected from light) and subjected to analysis of proximate composition, vitamin C, phytate, polyphenols, anthocyanins and antioxidant activity. The drying process had little effect on the proximate composition of the flour, presenting significant difference only for crude protein, fiber and non-nitrogenous extract. The greatest preservation of chemical constituents occurs in the lyophilized jaboticaba skins. Among the drying temperatures tested, however, the skins dried at 45 and60Â°C had more highly preserved nutritional substances and antioxidants.Â